Low Contrast Agent and Radiation Dose Protocol for Hepatic Dynamic CT of Thin Adults at 256–Detector Row CT: Effect of Low Tube Voltage and Hybrid Iterative Reconstruction Algorithm on Image Quality - Nakaura, Takeshi; Nakamura, Shinichi; Maruyama, Natsuki; Funama, Yoshinori; Awai, Kazuo; Harada, Kazunori; Uemura, Shouzaburou; Yamashita, Yasuyuki (Radiology, 2012)
To evaluate the effect on image quality of a low contrast agent dose and radiation dose protocol at abdominal dynamic computed tomography (CT) with a low tube voltage, hybrid iterative reconstruction algorithm, and a 256- detector row scanner. This prospective study received institutional review board approval, and prior informed written consent was obtained from all patients. Seventy-four patients undergoing hepatic dynamic CT were randomly assigned to one of two protocols: Thirty-nine patients underwent scanning with the conventional 120-kVp protocol and the other 35 patients underwent scanning with an 80-kVp tube voltage and a 40% reduction in contrast agent dose. The 80-kVp images were also postprocessed with a hybrid iterative reconstruction algorithm. The estimated effective radiation dose of each protocol was compared and the image noise and contrast-to-noise-ratio (CNR) of the 120-kVp, 80-kVp, and hybrid iterative reconstructed 80-kVp images were evaluated by using the Student t test. The effective radiation dose was 51% lower during the hepatic arterial phase (HAP) and 48% lower during the portal venous phase (PVP) with the 80-kVp protocol than with the 120-kVp protocol (HAP: 5.6 mSv ± 1.0 [standard deviation] vs 11.6 mSv ± 3.3; PVP: 5.8 mSv ± 0.7 vs 11.2 mSv ± 3.2, respectively). The hybrid iterative reconstruction decreased image noise by 23% during the HAP (9.2 ± 1.9 vs 12.0 ± 2.6) and by 24% during the PVP (9.4 ± 1.8 vs 12.3 ± 2.6). There were no significant differences in the CNR of any of the regions of interest between 80-kVp with iterative reconstruction and 120-kVp protocols (P = .46-.85). A low tube voltage and the hybrid iterative reconstruction algorithm can dramatically decrease radiation and contrast agent doses with adequate image quality at hepatic dynamic CT of thin adults with use of a 256-detector row scanner.